Lifestyle in children and adolescents with obesity: results of the survey of patients and their parents - Alisa V. Vitebskaya (Ожирение и метаболизм, 2016)
Introduction. Growth of obesity prevalence in children and adolescents is a serious problem of modern medicine. To learn characteristics of patient’s behaviour, their dietary preference, feeding time and physical loads one can use specialized questionnaires.Aim. Evaluation of lifestyle, physical activity, dietary regimen and consumption of some meals according to results of questioning childrenand adolescents with obesity and their parents.Materials and methods. Hundreds of children and adolescents with obesity 10–17 years and their parents answered the questionnaire onage of obesity onset, its causes, physical activity and nutrition.Results and conclusion. Obesity develops more often at the age of 7–10 years. The most commonly insufficient physical activity and heredity. Specific characteristics of sedentary lifestyle and impared dietary regimen were identified. Comparison of patients’ and parents’ answers allowed to demonsrate the differense in attitude to the problem of obesity and to diminish the influence of not transparant answers on the results of investigation.